2014
DOI: 10.2478/s11535-013-0276-8
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the in vitro cytotoxic and antiviral activities of different medicinal plants against infectious bursal disease (IBD) virus

Abstract: Infectious bursal disease (IBD) caused by non-enveloped double stranded RNA virus is an acute and contagious poultry disease. Outbreak of IBD could result in 10-75% mortality of the birds; hence it has gained socio-economic importance worldwide. Medicinal plants have shown broad spectrum anti-viral activities against RNA and DNA viruses. Moringa oleifera Lam (MOL), Phyllanthus emblicus Linn (PEL), Glycyrrhiza glabra Linn (GGL), and Eugenia jambolana Lam (EJL) are commonly available medicinal plants of the sub-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…Previous research showed that jamun fruit crude extract exhibited cytotoxic activity against MCF 7, Hela Cervic carcinoma cell lines, Hep G2 liver carcinoma cell lines, H 460 lung carcinoma cell lines, and U251 brain carcinoma cell lines 21,22 , but not on hPBMCs. Waqas Ahmad et al, 23 used Jamun leaf powder to study the cytotoxic effects on Vero cell lines with a maximum concentration of 100 µg/mL, and almost agreement percent cell survival was noted in our study also 24 .…”
Section: Discussionsupporting
confidence: 78%
“…Previous research showed that jamun fruit crude extract exhibited cytotoxic activity against MCF 7, Hela Cervic carcinoma cell lines, Hep G2 liver carcinoma cell lines, H 460 lung carcinoma cell lines, and U251 brain carcinoma cell lines 21,22 , but not on hPBMCs. Waqas Ahmad et al, 23 used Jamun leaf powder to study the cytotoxic effects on Vero cell lines with a maximum concentration of 100 µg/mL, and almost agreement percent cell survival was noted in our study also 24 .…”
Section: Discussionsupporting
confidence: 78%
“…Ethanolic extract of leaves showed negative activity for herpes simplex virus (HSV; Lipipun et al, ) and seeds against HSV‐1 (Ali, El‐Taweel, & Ali, ). Ethanolic extract of leaves showed significant antiviral activity against infectious bursal disease virus (Ahmad et al, ), foot and mouth disease virus, equine herpes virus, hepatitis virus, and rhinovirus (Younus et al, ). Leaf aqueous extract activated the cellular immunity in infected mice with HSV‐1 by decreasing the infection rate and reducing herpetic skin lesion growth (Kurokawa et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Probably, the reduction observed in the pgRNA of genotype H was not enough to reduce the rate of replication of the virus, but the antifibrotic and antioxidant effects deduced by the changes in CTGF , TGFβ , and CAT gene expressions with M. oleifera treatment support the fact that Moringa might be used as a valuable nutritional supplement for patients with chronic hepatitis B. There are additional studies, both in vivo and in vitro , reporting effects of M. oleifera in different viruses, like herpes simplex virus type 1 [ 20 ], Epstein-Barr virus [ 21 ], Newcastle disease virus [ 22 ], and infectious bursal disease virus [ 23 ]. Nevertheless, the complete elucidation of the molecular mechanisms driving M. oleifera action remains to be defined.…”
Section: Discussionmentioning
confidence: 96%